The calf became an orphan : A study in contemporary Kannada fiction - Robert J. Zydenbos (Institut Français de Pondichéry, 1996)
This book is a revised version of a Ph. D. Thesis submitted to the University of Utrecht. It is the first doctoral dissertation about Kannada literature submitted at a university in the Western world. The book is an attempt at learning about the culture of Karnataka as reflected in contemporary Kannada fiction. It surveys Kannada fiction of the post-Independence era, in the light of certain "culturally specific themes". Through a literary analysis of 35 works, the author of the book has focused on such themes as Indian womanhood, aspects of Hinduism, its confrontation with other faiths, the implications of the caste system and so on. The book contains elaborate summaries of the literary works discussed.